2002
DOI: 10.1034/j.1600-051x.2002.290213.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin‐1 gene polymorphism in a periodontally healthy Hispanic population treated with mucogingival surgery

Abstract: Within the limits of this study it is concluded that (1) periodontal health can be maintained with proper preventive maintenance irrespective of the genotype present, (2) the mean response to mucogingival surgery to cover localized gingival recessions is similar irrespective of the IL-1 periodontal genotype, however, full coverage is achieved more frequently in genotype negative subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 14 publications
0
23
1
1
Order By: Relevance
“…The present study has yielded a percentage of 16.66%, the prevalence of which is lower when compared to the previous studies,[111720] but higher when compared to the prevalence of 11.66% observed among the Maharashtrian ethnic group. Further larger studies may be needed to corroborate these results.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The present study has yielded a percentage of 16.66%, the prevalence of which is lower when compared to the previous studies,[111720] but higher when compared to the prevalence of 11.66% observed among the Maharashtrian ethnic group. Further larger studies may be needed to corroborate these results.…”
Section: Discussioncontrasting
confidence: 77%
“…Several studies have shown variations in the distribution of composite genotype in association with periodontitis patients from different geographic areas and ethnic groups. [11131720] Studies examining ethnic population from Europe have reported consistently that approximately 30% of the individuals are genotype positive. Walker et al .…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the frequencies found in Caucasians for the different genotypes, the IL-1 genotype was detected at a very low prevalence (2.3%) in Chinese subjects and at 22.5% in African Americans subjects (12,13). Recently, a frequency of 26% for the composite genotype was reported in subjects of Hispanic heritage (n ¼ 22) resident in the USA (21). However, this study was conducted on healthy subjects in order to investigate the outcomes of a mucogingival therapy, and not on patients with periodontitis.…”
Section: Discussionmentioning
confidence: 76%
“…3), 4) This might be due to the fact that the membranes seldom provided PDL cell promoting effect. Therefore, development of active material for PDL cell promotion seems to be reasonable to solve this dilemma.…”
Section: Introductionmentioning
confidence: 99%
“…Each sample was washed twice in 0.1 M phosphate buffered saline and fixed with 2.5 glutaraldehyde for at least 10 minutes. The complexes were then incubated for 10 minutes in a postfixative of 1 aqueous OsO 4 and subsequently washed twice with phosphate buffer for 10 minutes. Samples were dehydrated through ascending ethanol (70, 90, 95 and 100), allowed to air dry overnight and shadowed with 20 nm Au/Pd.…”
Section: 4mentioning
confidence: 99%